Criminal Provisions For Perpetrators Who Commit Criminal Acts of Copulation And Lewd Acts Against Minors - Diana, Diana; Prawesthi, Wahyu; Amiq, Bahrul (Indonesian Journal of Law and Justice, 2024)
The frequency of these crimes, one of which is the unlawful act of sexual abuse, which encompasses both fornication and copulation, demonstrates the current high rate of crimes against children. Children and the future of the nation are seriously and dangerously at stake from this. Sexual activity is a crime that seriously damages society, it is taken very seriously, and it makes people feel uneasy since it incites a dread of crime. Data collection, processing, presentation, and analysis related to an event constitute the process of research. to acquire a study outcome that is responsible for science. Normative juridical research is the kind that is employed. Articles 81 and 82 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection discuss the legal provisions for child molestation against children.